DAMPAK PENGGUNAAN SMARTPHONE TERHADAP INTERAKSI SOSIAL ANAK USIA 3-5 TAHUN (STUDI KASUS PADA ANAK DENGAN LATAR BELAKANG ORANG TUA KARIR) - Monica Monica; Ni'matul Hikmah; Latifah Firdaus (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2018)
This survey is for knowing the effect of smartphone to social interaction, the children ager 3-5 years considered from parents career background. Smartphone is a device that enable to do a communication ( like phone or sms ) and also there is PDA function ( Personal Digital Assisten ) and her capability like a computer. Meanwhile, social interaction is a correlation between two or more persons, where an individual behavior or on the countrary. This survey is done using qualitative descriptive with case study method. This survey is done to 3 subjects who study in 2 KB in Sleman District. With the intensity of using smartphone is high categorised. The result of the survey shows that there is negative effect from the using of smartphone to children social interactionin school environment. From the three subjects have similarity, that is the difficulty in socialization of the same age friends, the effect of using smartphone without time controlling and checking from parents who have business in job environment.